Synthesis, Characterization and Antibacterial Activity of Silver Nanoparticles Prepared from Benzoin Gum (Loban) Extract - Arsalan Mukhtar; Aleem Munir; Dawood Ahmed (RADS Journal of Biological Research & Applied Science)
Background: The rise of multi-drug resistance poses a significant challenge for treating infectious diseases. Nanotechnology-particularly the use of silver nanoparticles (AgNPs)-offers promising solutions.